Globalisation, Land Alienation and its Impact on the Right to Livelihood of the Tribal Communities in Kerala - Aditya V. Nair and Vishnu V. S (Sociology and Anthropology, 2018)
India has the second largest tribal in the world. According to the 2011 Census, tribes constitute 2% of the total population. India has around 461 ethnic groups and they constitute India’s indigenous population. India has provided the tribal communities with several protections through laws and constitutional provisions. Despite this they are suffering from many problems. Globalisation ushers in mammoth changes which influence the social, economic, political and even cultural scenario of a country. In India, the mainstream globalisation model has neglected the inclusive growth of economy and has largely concentrated on promotion of gross domestic product, thus creating unhealthy consequences. Its impact has been drastic on the tribal who have been displaced in large numbers by developmental projects which have ignored effective rehabilitation. The neo-liberal movement has not only deprived them of their identity but also their livelihood rights pushing them into abject poverty. The impact of globalisation on the tribal life is also evident in the State of Kerala. The 2011 census report records the overall tribal population in the state as 4,84,839. There are 36 tribal communities across Kerala and ‘Paniya’ tribes are the biggest tribes among them. The highest concentration of Scheduled Tribes in Kerala is in Wayanad followed by Idukki. The rapid technological advancement and interplay of market forces and the rising power of neo liberalism has led to eviction of the tribal from their land, denying them a right to live with human dignity. Examples of such invasions are ample in the State of Kerala. The paper discusses the impact of globalisation on the Tribal community in Kerala. It seeks to find answers and give suggestions as to how globalisation must be managed in a sustainable manner, respecting the rights of tribal people particularly their right to livelihood. The paper concludes by making suggestions as to how globalisation must be made more sustainable, keeping in view the rights of Tribal communities in Kerala. Strong steps to be taken by the Government to mobilise more assistance to these communities. Any growth model that is adopted must give due respect to the rights of subsistence and cultural identity of these communities. The impact of globalisation should be such that it makes those who already have a comfortable existence more comfortable and plunge the others into a more dilapidated state.